A Quantitative Analysis of the Mixing of Three Solids Different in Density by an Air Fluidized Bed - H. Sulaymon, Abbas; Habeb Salman, Rasha (Iraqi Journal of Chemical and Petroleum Engineering, 2008)
Three cohesionless free flowing materials of different density were mixed in an air fluidized bed to study the mixing process by calculating performance of mixing index according to Rose equation (1959) and to study the effect of four variables (air velocity, mixing time, particle size of trace component and concentration of trace component) on the mixing index and as well as on mixing performance. It was found that mixing index increases with increasing the air velocity, mixing time and concentration of trace component until the optimum value. Mixing index depends on the magnitude of difference in particle size The first set of experiments (salt then sand then cast iron) give higher mixing index and better performance of mixing than the second set of experiments (sand then salt then cast iron). Box-Willson method was used to minimize number of experiments and to represent the relationship between the variables.